The Optimal Distribution of Practice for the Acquisition of L2 Morphology: A Conceptual Replication and Extension. Issue 3 (23rd March 2017) - Suzuki, Yuichi
Abstract: This study examined optimal learning schedules for second language (L2) acquisition of a morphological structure. Sixty participants studied the simple and complex morphological rules of a novel miniature language system so as to use them for oral production. They engaged in four training sessions in either shorter spaced (3.3‐day interval) or longer spaced (7‐day interval) learning conditions. From the beginning of the third training session, the 3.3‐day interval group started to provide more accurate target rules than the 7‐day interval group. This superior performance by the 3.3‐day interval group was maintained on both 7‐ and 28‐day delayed posttests with small to medium effect sizes. No significant difference was found between the two groups for utterance speed, nor did linguistic complexity exert an influence on the effectiveness of different distributions of learning conditions. Open Practices: This article has been awarded an Open Materials badge. All materials are publicly accessible in the IRIS digital repository athttp://www.iris-database.org . Learn more about the Open Practices badges from the Center for Open Science:https://osf.io/tvyxz/wiki .